Implementation of the steam learning model in pgmi on the creativity of prospective students of madrasah ibtidaiyah teachers at stai al hikmah tanjung balai: A descriptive qualitative study - Intan Rahmadania; Irmayanti Mangunsong (At Turots: Jurnal Pendidikan Islam, 2025)
This paper aims to analyze the implementation of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning model in enhancing the creativity of students in the Elementary School Teacher Education Program (PGMI) of STAI Al Hikmah Tanjung Balai. The background of this research is based on the need to strengthen the creativity of prospective MI teachers so they are able to design innovative and relevant learning to meet the demands of the digital era. This research uses a descriptive qualitative approach through observation, interviews, and documentation of lecturers and students who attended STEAM-based lectures. The results show that the implementation of STEAM learning can improve students' creative thinking, collaborative thinking, and problem-solving skills through project activities that integrate elements of science, technology, arts, and mathematics in the context of Islamic education. Lecturers act as facilitators who encourage the exploration of students' ideas, while supporting factors for implementation include the availability of digital media and institutional support; while constraints include limited facilities and lecturers' readiness in cross-disciplinary integration. Overall, this research contributes to strengthening the theoretical and practical foundations of STEAM implementation in Islamic higher education and provides implications for the development of a more innovative PGMI curriculum to foster creativity and professional readiness of prospective MI teachers.